Biochar amendment alters rare microbial taxa and enhances wheat growth in alkaline farmland: insights into soil microbiome dynamics - Qi, Jian-Qing; Yuan, Hai-Yan; Sun, Shu-Chen; Zama, Eric Fru; Tao, Bao-Xian; Liu, Jin; Zhang, Bao-Hua (Frontiers in Microbiology, 2025)
IntroductionBiochar is recognized as a promising soil amendment for maintaining soil fertility and improving soil conditions. Alkaline farmland is widely distributed globally. Soil microbial taxa, including rare, intermediate, and abundant bacteria, fungi, protists, and phoD-harboring microbes, play essential roles in carbon, nitrogen, and phosphorus cycling. However, the impacts of biochar on the community composition of these taxa in alkaline farmland are not well understood. Gaining insights into how the soil microbiome responds to biochar application and its association with crop biomass is crucial for sustainable agriculture. In particular, the responses of rare microbial communities, such as rare protists and phoD-harboring microbial taxa, to biochar and their relationship with crop biomass remain largely unexplored.MethodsIn this study, topsoil (0–10 cm) samples were collected from a three-year field experiment in a wheat (Triticum aestivum cv. Jimai 22)-maize (Zea mays cv. Jiyuan 169) rotational cropping system. The experiment included treatments with and without biochar application (CK). Gene abundance of bacterial 16S rRNA and phoD, a gene encoding an alkaline phosphatase involved in phosphorus cycling, was quantified using quantitative polymerase chain reaction (qPCR). The compositions and diversities of bacterial, fungal, protistan, and phoD-harboring microbial communities were analyzed by Illumina MiSeq sequencing.ResultsBiochar application significantly reduced soil total phosphorus (TP) and ammonium nitrogen (NH4+-N) contents. It increased soil N:P ratios by 19.63%, 2.80%, 23.36%, and 27.10% in B0.5, B1.0, B1.5, and B2.0 treatments, respectively. Soil dissolved organic carbon (DOC) positively correlated with bacterial 16S rRNA gene abundance, while total nitrogen (TN) linked to the ratio of phoD to bacterial 16S rRNA gene abundance and rare protistan taxa. In terms of crop yield, the B1.5 treatment (3.42 t ha−1) increased wheat yield by 35% compared to the CK treatment. Mantel test and random forest analyses indicated that rare phoD-harboring, protistan, and fungal communities significantly contributed to wheat growth.DiscussionThis study offers valuable insights into the effects of biochar on soil microbiomes, especially the responses of abundant, intermediate, and rare taxa. The changes in soil nutrient contents and the correlations between soil properties and microbial communities suggest that biochar can modify the soil environment and microbial structure. The significant contribution of rare microbial communities to wheat growth emphasizes their importance in maintaining agricultural ecosystem health and ensuring sustainable ecosystem services. These findings can guide the rational application of biochar in alkaline farmland to promote sustainable agriculture.